2020
DOI: 10.3390/en13205342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Struvite Recovered from Anaerobic Digestate in a Farm Bio-Refinery as a Slow-Release Fertiliser

Abstract: Biogas production in agricultural biogas plants generates digestate—liquid waste containing organic matter and mineral nutrients. Utilisation of the digestate on farm fields adjacent to the biogas plants is limited. Therefore, bio-refineries implement advanced forms of digestate processing, including precipitation of struvite (MgNH4PO4.6H2O). Struvite can be transported over long distances and dosed precisely to meet the nutritional needs of the plants. Divergent opinions on the fertilising value of struvite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…8B). Similar considerations have been made in the case struvite [40][41][42]. In addition, Grigatti et al [43] showed that the solid fraction of AD of maize had the highest potential P availability (Olsen-P) in comparison to inorganic P source (Ca(H 2 PO4) 2* H 2 O), in line with our results.…”
Section: Second Growth Cyclesupporting
confidence: 92%
“…8B). Similar considerations have been made in the case struvite [40][41][42]. In addition, Grigatti et al [43] showed that the solid fraction of AD of maize had the highest potential P availability (Olsen-P) in comparison to inorganic P source (Ca(H 2 PO4) 2* H 2 O), in line with our results.…”
Section: Second Growth Cyclesupporting
confidence: 92%
“…Traditional P fertilizers come from rock phosphate, which nowadays is a limited resource and will be depleted within the next 150-250 years [7,8] and thus P is subject to special attention [9]. Recovery of P is limited to the agriculture sector because this sector is mostly based on P and materials rich in this element can be found [10][11][12]. Therefore, as a result, there is growing interest in the efficient recovery of nutrients from waste.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting source of P supply for farms is STR (magnesium ammonium phosphate) [15]. It is an alternative P fertilizer with valuable properties containing macro elements needed by plants [10,16,17]. This fertilizer is still not implemented as a mineral fertilizer under general EU regulations, but these are currently being revised to recommend the allowance of STR into the EU fertilizer market [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In this system, natural recycling of P is prevented by excessive anthropogenic input and waste and most P applied in agriculture is not utilized, with only 15-20% of the P in PR reaching the food consumed globally (Sutton et al 2013). Underutilized P accumulates in soil and 39.5% of P is lost through erosion and run-off (Lun et al 2018), exacerbating eutrophication, triggering harmful algal blooms (HABs) and creating hypoxic dead zones in water bodies (CRS 2020; US EPA 2021) (Carpenter et al 1998;Szymańska et al 2020). The economic cost of eutrophication in the US was estimated to be over $2.2 billion annually in 2008 (Dodds et al 2008) and is expected to be much higher today.…”
Section: Introductionmentioning
confidence: 99%